A pilot study on the feasibility and initial outcomes of a telerehabilitation system for balance and cognitive training in older adults - Sedivcova, Milada Luisa; Mothejlova, Karla; Hana, Karel; Kaspar, Jan; Buchtelova, Aneta (Biomedical papers, 2025)
Aims. This randomized controlled multicentric pilot study aimed to evaluate the feasibility, safety, and preliminary clinical efficacy of a home-based telerehabilitation system for improving balance and cognitive function in older adults.Methods. The study was conducted in two four-week phases across multiple centres. In Phase A (n=18), participants were randomized into an experimental group (n=10) using a telerehabilitation balance training module (Stability Module) and a control group (n=8) receiving standard kinesiotherapy. In Phase B (n=11), a second cohort was randomized into an experimental group (n=5) receiving combined balance and cognitive training (Stability + ActiveCOG Modules) and a control group (n=6) receiving standard therapy. Outcomes were measured using the Berg Balance Scale (BBS) and Mini Mental State Examination (MMSE). Statistical analysis included paired t-tests, Fisher's exact test, Wilcoxon rank-sum test, and effect size estimation using Cohen's d.Results. In Phase A, both the experimental and control groups showed significant within-group improvements in balance (BBS: P=0.004 and P=0.041, respectively), with no significant difference between groups. In Phase B, the intervention group demonstrated significant within-group improvements in both balance (BBS: P=0.009) and cognitive function (MMSE: P=0.034), while between-group differences did not reach statistical significance (P≥0.05). Effect sizes in Phase B suggested substantial clinical relevance (Cohen's d>1.0).Conclusion. The study confirmed the feasibility and safety of the telerehabilitation system and highlighted its usability in home environments. While preliminary clinical improvements were observed, particularly with combined motor-cognitive training, the small sample size limits definitive conclusions. These findings support the feasibility of larger, longer-term trials to further evaluate clinical efficacy and scalability.
Keywords: telerehabilitation; older adults; balance training; cognitive training; dual-task intervention